Cellular Localization of PACAP and Its Receptors in the Ovary of the Spotted Ray Torpedo marmorata Risso 1880 (Elasmobranchii: Torpediniformes). Issue 1 (1st October 2012) - Agnese, Marisa; Valiante, Salvatore; Laforgia, Vincenza; Andreuccetti, Piero; Prisco, Marina
Abstract The pituitary adenylate cyclase‐activating polypeptide (PACAP) is a member of the glucagon‐related family and occurs in two amidated forms, PACAP38 and PACAP27, with 38 and 27 amino acids, respectively. PACAP acts by binding to three different receptors, that are classified by their binding affinity for PACAP and VIP (vasoactive intestinal polypeptide): PAC1R (PACAP‐specific receptor) exclusively binds PACAP, while VPAC1R (VIP/PACAP receptor, subtype 1) and VPAC2R (VIP/PACAP receptor, subtype 2) bind both PACAP and VIP. PACAP, first discovered in the brain, was then localized in several peripheral tissues of mammals, including the ovary. Besides mammals, PACAP and its receptors have been reported in fish too; however, less is known about the presence of PACAP in the fish ovary and the studies are limited to teleosts. The aim of our work was to study the distribution of the PACAP/PACAP‐Rs system in the ovary of the cartilaginous fish Torpedo marmorata. Using in situ hybridization (ISH) and immunohistochemistry techniques, we demonstrated that PACAP and its receptors are widely represented in the Torpedo ovary in a stage‐dependent manner. Moreover, our findings suggest an involvement of this peptide in the whole follicologenesis, probably influencing steroidogenesis, follicle development, and oocyte growth. J. Exp. Zool. 319A:1–9, 2013. © 2012 Wiley Periodicals, Inc.